Enhanced production of IGF‐I in the lungs of fibroproliferative ARDS patients. Issue 11 (3rd November 2014) - Andonegui, Graciela; Krein, Peter M.; Mowat, Connie; Brisebois, Ronald; Doig, Christopher; Green, Francis H. Y.; Léger, Caroline; Winston, Brent W.
Abstract Insulin‐Like Growth Factor I (IGF‐I) has been identified in the lungs of individuals with fibrotic lung diseases. In a previous retrospective study, we showed enhanced IGF‐I immunoreactivity in individuals with fibroproliferative acute respiratory distress syndrome (FP‐ARDS), but we were unable to determine if this correlation was causative. This study was undertaken to prospectively investigate whether IGF‐I expression correlated with the fibroproliferative process and whether IGF‐I was induced and made in the lungs. We measured IGF‐I and procollagen III peptide (PCP‐III) in the epithelial lining fluid (ELF) from controls, early ALI/ARDS patients and FP‐ARDS patients. We also measured IGF‐I mRNA and immunoreactivity from controls and FP‐ARDS patient lung biopsies. We determined the level of lung permeability by measuring albumin and urea levels in ELF and serum. Our data show that IGF‐I is significantly increased in the ELF in FP‐ARDS patients. A significant correlation between IGF‐I and PCP‐III in the ELF of FP‐ARDS patients is found. IGF‐I mRNA is elevated in the FP‐ARDS lung biopsies. Our data suggest that IGF‐I found in the lungs of FP‐ARDS patients results from both increased lung permeability and local production of IGF‐I. The role of IGF‐I in the fibroproliferative process in the lungs has recently been confirmed in an animal model of lung fibroproliferation. This study importantly suggest that IGF‐I protein is made in the lungs of FP‐ARDS patients and correlates with increased levels of ELF PCP‐III, implicating a role for IGF‐I in the fibroproliferative process in humans.